Responsibility And Important Role of Notary in Ensuring The Validity of Land Sale And Purchase Deeds - Zaelani, Ivan (Syiar Hukum, 2024)
Notary has the responsibility and plays a crucial role as an authentic deed-making official in the land sector, with the notary Deed being the main source in maintaining the juridical data of land registration. One of the deeds made by notary is the Sale and Purchase Deed (AJB), which aims to ensure the legal certainty of the transfer of land rights. However, there are problems related to AJB that are not read directly by notary, but by notary office employees. This research analyzes the responsibility of the notary in the AJB read by the notary office employee using a qualitative juridical approach with literature study as a secondary data source. The results of the study concluded that notary has ethical and legal responsibilities in making AJB. Cancellation of AJB provides legal protection to good faith buyers, including the right to demand refunds, compensation, and interest.